Sports participation improves metabolic profile in adolescents: ABCD growth study - Cayres-Santos, Suziane Ungari [UNESP] (2019)
To analyze the impact of participation in sports with different cardiorespiratory fitness (CRF) demands on changes in metabolic and cardiovascular markers in adolescents. Longitudinal study with 12 months of follow-up (Analysis of Behaviors of Children During Growth [ABCD Growth Study]). Overall, 184 adolescents (age 15.6 ± 2.1) were classified according to sports participation: non-sport (control), low CRF sports, and high CRF sports. Metabolic outcomes were total cholesterol (TC) and its fractions, triacylglycerol (TG), glucose, insulin levels, and the insulin resistance index. Cardiovascular outcomes were arterial thickness (carotid and femoral [ultrasound]), blood pressure, and resting heart rate. Adolescents engaged in sports classified as high CRF demand presented a significant increase in HDL-c (1.2 mg/dL [95%CI: −0.5 to 3.0]) when compared to the non-sport group (−2.4 mg/dL [95%CI: −4.4 to −0.5]). Regular engagement in high CRF sports was significantly related to changes in TC (β = −0.027 [95%CI: −0.048 to −0.005]), HDL-c (β = 0.009 [95%CI: 0.001 to 0.019]), LDL-c (β = −0.032 [95%CI: −0.049 to −0.016]), and glucose (β = −0.017 [95%CI: −0.025 to −0.008]), while engagement in low CRF sports was related to changes in TG (β = −0.065 [95%CI: −0.112 to −0.019]). No significant relationships for cardiovascular parameters were observed in the low CRF group, but one significant relationship was found between high CRF sports and changes in SBP (β = −0.063 [95%CI: −0.117 to −0.009]). In conclusion, engagement in sports seems to be beneficial for improvements in metabolic and cardiovascular parameters in adolescents, mainly sports with higher CRF demand.